Influence Discovery Learning on Cognitive Skils and Science Process Skills of Grade VII Junior High School Students - Nasution, Elfira; Djulia , Ely; Ernawati, Nina (ISER (Indonesian Science Education Research), 2025)
This research aims to know the influence of Discovery Learning on the cognitive abilities and science process skills of grade VIII students. This study uses the method of the Quasi-Experimental Sampling technique using simple random sampling. The research sample consisted of two classes, namely class VII-4 (Experimental Class), which used the model Discovery Learning, and VII-5 (Control class), using learning direct instruction, each class consists of 31 students. The research instruments in this study were a multiple-choice cognitive ability test consisting of 30 questions and a science process skills observation sheet consisting of 19 statements. Data were analyzed using prerequisite tests and t-tests (independent sample t-tests). Based on the results of data analysis, there was a significant influence (sig 2-tailed) < 0.05, where 0.000 < 0.05 on cognitive abilities and Science Process Skills in the experimental class. Based on the hypothesis test, it was found that there was an influence of discovery learning on the cognitive abilities and science process skills of grade VII students on the solar system material at SMP Negeri 13 Medan, 2024/2025 academic year.